2019
DOI: 10.3390/nu11092241
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the Antioxidant Hydroxytyrosol from Tyrosol Present in Beer and Red Wine in a Randomized Clinical Trial

Abstract: Beer and wine contains the simple phenol tyrosol (TYR) which is endogenously converted into hydroxytyrosol (HT), one of the strongest dietary antioxidants, by CYP2A6 and CYP2D6 polymorphic enzymes. We investigated in humans the rate of this bioconversion after beer and red wine (RW) intake. In a single blind, randomized, crossover, controlled clinical trial (n = 20 healthy subjects), we evaluated TYR absorption and biotransformation into HT following a single dose of (i) RW, (ii) Indian pale ale beer (IPA), (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…Finally, in the context of non-alcoholic beer consumption, it is worth to mention the role that has been attributed to alcohol in promoting the bioavailability of phenolic compounds. This has been recently demonstrated with a reduced bioavailability of TYR following non-alcoholic beer consumption [31]. Therefore, non-alcoholic beers, which have a low concentration of phenolic compounds from the outset and an absence of alcohol, would represent a minor source of phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in the context of non-alcoholic beer consumption, it is worth to mention the role that has been attributed to alcohol in promoting the bioavailability of phenolic compounds. This has been recently demonstrated with a reduced bioavailability of TYR following non-alcoholic beer consumption [31]. Therefore, non-alcoholic beers, which have a low concentration of phenolic compounds from the outset and an absence of alcohol, would represent a minor source of phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of beer as a direct source of HT is negligible. Moreover, the presence of TYR in beer is relevant, since it has been demonstrated that dietary TYR is converted in humans into HT [30,31]. Both TYR supplementation and its biotransformation into HT are capable of triggering relevant beneficial effects on the cardiovascular system [30].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its high concentration, also thanks to high producing yeasts (see Section 5 , “The role of barley, yeast and hop genetics on beer phenols”), the simple phenolic alcohol tyrosol is one of the main phenols looked at in beer, present also in alcohol-free beers [ 10 ]. Concentration is so high in certain beers, reaching that of red wine [ 11 ], that authors have hypothesized that tyrosol could represent an indirect source, through biotransformation, of the more biologically active hydroxytyrosol [ 12 ] (see Section 6 , “Phenols-related health effects of beer consumption”). In alcoholic beers, both phenols possibly protect yeast from the stress generated by high levels of ethanol, a phenomenon that has been demonstrated for wine’s resveratrol [ 13 ], indicating that phenols not only undergo changes during brewing, but they also direct it.…”
Section: Main and Minor Beer Phenolsmentioning
confidence: 99%
“…The opposite effect of alcohol has been reported for tyrosol metabolization to hydroxytyrosol following beer consumption, as mentioned above. In particular, the administration of a single dose of 250 mL of blonde beer was associated to higher urinary recovery of tyrosol, whilst an identical dose of alcohol-free beer yielded higher urinary recovery of hydroxytyrosol [ 12 ]. However, as alcohol consumption proportionally increases hydroxytyrosol excretion through dopamine metabolism [ 105 ], hydroxytyrosol bioavailability is hardly attributable only to beer phenols.…”
Section: Phenols-related Health Effects Of Beer Consumptionmentioning
confidence: 99%
“…When these beverages are consumed, this simple phenolic compound is converted endogenously to hydroxytyrosol. This phenolic compound has been considered a powerful antioxidant in diets (Soldevila-Domenech et al, 2019). Temperature, alcoholic degree, sugar and amino acid concentrations, oxygen dissolved and pH have been influenced the glycerol biosynthesis, as well as in the production of aromatic compounds (Bordiga et al, 2016;Zhao;Procopio;Becker, 2015).…”
Section: H Nmr Analysis Of Juices and Fermented Beveragesmentioning
confidence: 99%